Tauroursodeoxycholic Acid (TUDCA) Regulates Inflammation and Hypoxia in Autonomic Tissues of Rats with Seizures - Üner, Arda Kaan; Okan, Aslı; Akyüz, Enes; Köklü, Betül; Eroğlu, Ece; Yilmaz, Seher; Ünalmiş, Demet; Kaymak, Emin; Aslan, Feyza Şule; Qureshi, Muhammad Zahid; Doğanyiğit, Züleyha (Cellular and Molecular Biology, 2023)
Inflammation and hypoxia have an effect on the molecular mechanism of cardiovascular and respiratory pathologies accompanying seizures. Against this, Tauroursodeoxycholic Acid (TUDCA) can regulate oxidative stress, inflammation and cellular survival by suppressing endoplasmic reticulum (ER) stress. We evaluated the expression changes of NF-κB p65, TNF-α, HIF1α and Kir6.2 proteins associated with seizures in brain stem, heart and lung tissues representing the autonomous network. Additionally, we examined the protective effects of TUDCA administration against damage caused by seizures in terms of immunohistochemistry and pathology. 4 groups of Wistar Albino male rats (250-300 g, n=32) were formed as control, pentylenetetrazole (PTZ), TUDCA and PTZ+TUDCA. The epilepsy kindling model was created by intraperitoneal (i.p.) injection of PTZ chemical (35 mg/kg, every 2 days) for one month. TUDCA (500 mg/kg; every 2 days) treatment was given intraperitoneally 30 minutes before seizures for 1 month. Brain stem, heart (atria, ventricle) and lung tissues of rats were isolated. NF-κB p65, TNF-α, HIF1α and Kir6.2 proteins in the obtained tissues were evaluated by immunohistochemical staining. The immunoreactivity of the investigated proteins in the brainstem heart and lung tissues of rats with chronic PTZ administration was significantly increased. Recurrent seizures led to accumulation of inflammatory cells in tissues, hemorrhage, vasodilation, and apoptosis. Following TUDCA administration, expression of NF-κB p65, TNF-α and Kir6.2 was significantly reduced in all tissues (except the atrium of the heart) compared to control rats. HIF-1α levels were significantly suppressed in ventricular and lung tissues of epileptic rats given TUDCA. However, TUDCA pretreatment improved histopathological changes due to chronic seizures and partially reduced apoptosis. We showed that epileptic seizures may cause tissue damage with the development of inflammatory and hypoxic conditions in the brainstem and organs that represent the autonomic network. TUDCA therapy could be an effective agent in the treatment of cardiac and respiratory problems associated with seizures.